Prediction of Lateral Grain Pressures in Flexible Containers - Elkhair, DOM; Unde, P A; More, H G (Journal of Agricultural Engineering, 2002)
The distribution of grain pressures on the walls of the cylindrical flexible containers are required for their design. The lateral grain pressures exerted by different grains on the walls of cylindrical polyethylene containers (varying in diameter from 30 to 60 cm, thickness from 0.10 to 0.20 mm and grain height from 20 to 100 cm) were calculated from measurements of the circumferential elongation in the containers, and prediction equations based on dimensional analysis were developed. The predicted values of lateral pressures were compared with the values of lateral pressures using Rankine’s and Janssen’s equations. The optimum container diameter and height were worked out. The developed mathematical models for different grains could predict the lateral grain pressures with an average prediction error between ± 3.12 % to ± 3.74 %. The optimum container diameter ranges from 60 to 90 cm whereas the optimum height ranged between 133 to 162 cm for all the grains.